1983
DOI: 10.1159/000137809
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of Benzodioxane &alpha;-Adrenoceptor Antagonists for &alpha;<sub>1</sub>-and &alpha;<sub>2</sub>-Adrenoceptors Determined by Binding Affinity

Abstract: A series of benzodioxane derivatives, structurally related to WB 4101 and piperoxan as well as prazosin and its two analogues UK-18,596 and UK-33,274, was studied with respect to their affinity for alpha 1-and alpha 2-adrenoceptors identified by 3H-prazosin (specific activity 33 Ci/mmol) and 3H-clonidine (specific activity 26.7 Ci/mmol), respectively, in isolated rat brain membranes. The structural variations made in these molecules gave rise to pronounced differences in affinity for alpha 1-adrenoceptors, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Some benzodioxanes such as doxazosin (Timmermans et al, 1980a) and the close structural analogue of ACC-7513, WB 4101 (Butler & Jenkinson, 1978;Mottram, 1980;Drew, 1982;Ruffolo et al, 1983) are selective for postsynaptic o-adrenoceptors, while others, e.g., piperoxan (Timmermans et al, 1980b) and RX 781094 (Dabire et al, 1981;Doxey et al, 1983) are selective for presynaptic receptors, and still others, may be relatively non-selective. In a recent binding study Timmermans et al (1983) concluded that benzodioxanes other than piperoxan and its analogues are selective for a,-adrenoceptors. If ACC-7513 should be fairly potent at presynaptic a-adrenoceptors this might account for the relatively small reductions in blood pressure observed, since reductions in blood pressure due to postsynaptic a-adrenoceptor blockade would be partially offset by the effective enhancement of sympathetic tone due to presynaptic x-adrenoceptor blockade.…”
Section: Vascular Smooth Muscle Relaxationmentioning
confidence: 99%
“…Some benzodioxanes such as doxazosin (Timmermans et al, 1980a) and the close structural analogue of ACC-7513, WB 4101 (Butler & Jenkinson, 1978;Mottram, 1980;Drew, 1982;Ruffolo et al, 1983) are selective for postsynaptic o-adrenoceptors, while others, e.g., piperoxan (Timmermans et al, 1980b) and RX 781094 (Dabire et al, 1981;Doxey et al, 1983) are selective for presynaptic receptors, and still others, may be relatively non-selective. In a recent binding study Timmermans et al (1983) concluded that benzodioxanes other than piperoxan and its analogues are selective for a,-adrenoceptors. If ACC-7513 should be fairly potent at presynaptic a-adrenoceptors this might account for the relatively small reductions in blood pressure observed, since reductions in blood pressure due to postsynaptic a-adrenoceptor blockade would be partially offset by the effective enhancement of sympathetic tone due to presynaptic x-adrenoceptor blockade.…”
Section: Vascular Smooth Muscle Relaxationmentioning
confidence: 99%